Policy to Protection: The Role of Human Nature and System Nature in Preventing Patient Injury - Roberts, Peter (Victoria University of Wellington Law Review, 2004)
This article examines theories and research relating to medical error. It looks at the human tendencies to err, to blame, and to trust. In light of the professionalism of health practitioners and the uniquely complex nature of the health system, the author encourages a focus on professionalism rather than consumerism. ACC’s abandonment of the concept of medical error is consistent with this approach to patient safety.